O fechamento das salas de cinema na cidade de Vitória e a política da Embrafilme para a produção do cinema nacional: projetando a própria crise! - Malverdes, André (2007)
This dissertation discuses the politics of Embrafilme towards Brazilian national cinema, specifically as related to the exhibition market in the city of Vitória from 1979 to 1985, as well as the reasons these theaters shut their doors permanently just as an overall dismantling of the Brazilian exhibition sector of the Brazilian cinematographic industry. Embrafilme is situated and contextualized in relationship to the national market in order to explain how this state company charged with aiding the national cinematographic industry during the military regime provided ample conditions for film production at the same time causing the closure of movie theaters. Focused on the movie-goers viewpoint, the work treats the act of “going to the show” as a social practice of the urban population in Vitória from the “Sidewalk theaters” to evidence of the effects of scarcity of a movie-going public on the local film exhibitors. The analysis demonstrates the most frequently viewed genres and the opinions of the exhibitors and movie-goers about the measures taken by Embrafilme, both in relationship to the production of feature films, principally the Pornochanchadas, or soft-care erotic films, and in its policies of obligating theaters to show national films for a determined number of days per year, even when faced with fierce competition from films imported into the national market, specifically the genres of adventure, Kung Fu, Western, comedy, musical comedy, drama, cartoons, and police movies, even including the hard core pornographic films after being liberated for theater exhibition. The work concludes identifying important social changes in the urban Capixaba public and observing how measures adopted by the military regime disarticulated the cinematographic industry in the city of Vitória.